Critical Thinking in Islam: What and How Its Practices - Muhammad Nurfazri; Ferli Septi Irwansyah (UIN Sunan Gunung Djati Bandung, 2024)
Studies on critical thinking in Islam, both in English and Arabic, are rare. From this an overview research, we explore the concept of critical thinking within Islamic tradition and its practices. A literature review is employed to collect the research data. The findings of this study showed that several points: foundations of critical thinking in Islamic teachings, the role of ijtihad, critical thinking according to Islamic philosophers, education and thinking in Islamic context, and practical applications of critical thinking in Islam. This overview research highlights that the principles of critical thinking are an integral part of the Islamic intellectual tradition and remain necessary for the religion's engagement with the modern world. Hence, it is hoped to open insight into Islamic critical thinking. Apart from that, it will be useful for further research in exploring the potential of critical thinking in Islamic tradition and applying it to a better Muslim life.